2021
DOI: 10.1016/j.jcjo.2020.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography angiography analysis of the retina in patients recovered from COVID-19: a case-control study

Abstract: Objective To quantify the density of the macular microvasculature and the area of the foveal avascular zone (FAZ) in patients recovered from Coronavirus Disease 2019 (COVID-19) using optical coherence tomography angiography (OCTA) analysis. Methods In a comparative cross-sectional, observational study, patients recovered from COVID-19 were included in this study. All included subjects exhibited a reverse transcription-polymerase chain reaction (RT-PCR) - confirmed diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
143
2
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(157 citation statements)
references
References 25 publications
(32 reference statements)
8
143
2
4
Order By: Relevance
“…In a recent study by Abrishami et al, OCTA was performed at least 2 weeks after recovery from systemic COVID-19 and mean SCP VD and DCP VD were significantly reduced in the COVID-19 cohort versus the age-matched controls. 2 FAZ area was also greater in the COVID group, but this did not reach statistical significance. In the present study, where all patients were hospitalized in contrast to the study by Abrishami et al, parafoveal SCP VD (nasal and superior quadrants) and DCP VD (all 4 quadrants) values were significantly lower compared with controls, whereas an increase in CC flow area was evident, but the 2 groups were similar in terms of FAZ.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…In a recent study by Abrishami et al, OCTA was performed at least 2 weeks after recovery from systemic COVID-19 and mean SCP VD and DCP VD were significantly reduced in the COVID-19 cohort versus the age-matched controls. 2 FAZ area was also greater in the COVID group, but this did not reach statistical significance. In the present study, where all patients were hospitalized in contrast to the study by Abrishami et al, parafoveal SCP VD (nasal and superior quadrants) and DCP VD (all 4 quadrants) values were significantly lower compared with controls, whereas an increase in CC flow area was evident, but the 2 groups were similar in terms of FAZ.…”
Section: Discussionmentioning
confidence: 68%
“… 1 Retina in particular has ACE and ACE-2 receptors in the choroid and on different cell types such as the Muller cells, ganglion cells, photoreceptor cells and the retinal vascular endothelial cells. 1 , 2 …”
mentioning
confidence: 99%
“…There were no significant differences in these parameters between hospitalized and non-hospitalized COVID-19 patients. 1 Similarly, findings from another study suggested an impairment in the blood supply to the peripapillary retinal nerve fiber layer in patients who recovered from SARS-CoV-2, but microvascular impairment was more evident in older patients and in patients with systemic hypertension. 2 However, the study by Abrishami and colleagues included patients who were young and otherwise healthy.…”
mentioning
confidence: 89%
“…In this issue, a comparative cross-sectional observational study by Abrishami and colleagues sheds light on the impact on the foveal avascular zone (FAZ) and vessel density of the deep and superficial macular capillary plexus in patients recovered from COVID-19 compared to age-matched healthy control subjects. 1 Thirty-one patients with at least one positive COVID-19 reverse-transcriptase polymerase chain reaction test were enrolled. Confounding variables such as ocular comorbidities (retinal disease, glaucoma, refractive error >5D), media opacity, or best-corrected vision less than 20/20 were excluded.…”
mentioning
confidence: 99%
See 1 more Smart Citation